A systems‐theoretic articulation of stakeholder needs and system requirements. Issue 2 (13th January 2021) - Salado, Alejandro
Abstract: The literature shows disparities in how fundamental systems engineering concepts in the area of requirements engineering, such as stakeholder needs, system requirements, requirements elicitation, requirements derivation, and requirements decomposition, are used within the communities‐of‐practice and in research. Such disparities can lead to conceptual and application inconsistencies, which have been shown to contribute to the formulation of poor requirements. In this paper, such concepts are articulated using systems theory as the underlying theoretical framework. The concepts of problem space, solution space, open system, and closed system are central to this work. It is argued that the proposed articulations facilitate avoiding usage disparity, ultimately resulting in better formulation of requirements. These articulations are supported by in‐depth examples that comprehensively cover different types of needs and requirements, and provide step‐by‐step insights into how elicitation, derivation, and decomposition occur within a problem formulation effort.